SISTEM PENDUKUNG KEPUTUSAN LATIHAN GERAKAN FITNESS BAGI PEMULA MENGGUNAKAN METODE WEIGHTED PRODUCT - Robby Rahmatullah; Wahyu Adimahendra (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Agna Physque Gym was ﬁtness center located in Gemolong District. Agna Physque Gym provided adequate services and facilities as well as eﬀortted to foster public interest in sports. The training program for beginners certainly required guidance from a personal trainer in compiling an exercise program that was in accordance with the desired target. Members of Fitness had problemed in determining an exercise program. This was a diﬃculty in determining the training program to be carried out. Study aimed to built a Decision Support System to determined the Fitness using the Weighted Product. The Weighted Product used multiplication to connected attribute ratings, where the rating of each attribute might be raised to the ﬁrst power with the weight of the attribute in question. This process was the same as the normalization process. programming language Java and the database used MySQL. This system could generated a ranking alternatif exercise program Fitness body weight user Based on the system testing carried out, the system could to provided results in accordance with the calculations used, so that this system could assisted in determining ﬁtness exercise recommendations.